Unpacking the tensions between local and national skills policy: employers, colleges and Local Enterprise Partnerships as collaborative anchors. (30th November 2022) - James Relly, Susan; Robson, James
Abstract : Inherent tensions exist in skills policies that aim to combine national economic growth and productivity with localised implementation for education and training. This is particularly apparent in the over-emphasis on employer engagement in national education and training policy, where the localisation of skills formation is particularly envisioned through employer engagement. Yet further education colleges have acted as anchors within local skills ecosystems working successfully with employers, often through Local Enterprise Partnerships (LEPs), providing the key bridging mechanism between national skills policy and localised enactment. We unpack the tensions between national and local skills policy by presenting a case study of a local skills ecosystem. Through interviews with key stakeholders – representatives from the local college, the LEP, and employers – we deploy Stephen J. Ball's approach to policy enactment to map the complex processes and tensions involved in the translation of national skills policy into local skills systems. Our findings highlight the critical role of colleges as anchor institutions in local skills ecosystems, with employers and LEPs working as 'collaborative anchors' in the policy cycle. We present the concept of 'local collaborative anchors' as a heuristic device for understanding tensions within local skills ecosystems and national skills policy enactment.